2013
DOI: 10.1111/ijfs.12331
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Escherichia coli O157 to chitosanarginine in beef liquid purge is affected by bacterial cell growth phase

Abstract: Summary Here, we evaluated the impact of bacterial growth stage on the effect of chitosan‐arginine (Ch‐arg) on Escherichia coli O157:H7 cell numbers and metabolic activity within contaminated beef juice held at room temperature. Using a lux‐marked metabolic reporter strain of E. coli O157:H7, the results showed that Ch‐arg was most bioactive against cells in the lag phase and exponential phase. In comparison, there was a reduced, although still significant, inhibitory effect of Ch‐arg on the viability and meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Chitosan has been conjugated to several cationic amino acids as well as peptides (Figure ). The synthesis of chitosan–arginine and chitosan–guanidine conjugates has been observed in many studies. , The carboxyl group of arginine was first activated by NHS/EDC at a first molar ratio and then coupled to the amino group of chitosan during different reaction times. This resulted in chitosan–arginine derivatives having DS in the range 0.08–0.28 .…”
Section: Antimicrobial Chitosan Derivativesmentioning
confidence: 99%
“…Chitosan has been conjugated to several cationic amino acids as well as peptides (Figure ). The synthesis of chitosan–arginine and chitosan–guanidine conjugates has been observed in many studies. , The carboxyl group of arginine was first activated by NHS/EDC at a first molar ratio and then coupled to the amino group of chitosan during different reaction times. This resulted in chitosan–arginine derivatives having DS in the range 0.08–0.28 .…”
Section: Antimicrobial Chitosan Derivativesmentioning
confidence: 99%
“…The disagreement in antimicrobial properties is attributed to the differences in the degree of deacetylation and a molecular weight between chitosan and chitooligosaccharide (No et al., ; No, Young Park, Ho Lee, & Meyers, ; Tsai et al., ). Other influencing factors include the initial microbial load, pH, concentration and type of biopolymer, temperature, and nature of the food (Alishahi & Aïder, ; Ganguly, ; Kumirska et al., ; Lahmer, Jones, Townsend, Baker, & Williams, ).…”
Section: Chitosan and Chitooligosaccharidementioning
confidence: 99%
“…It was demonstrated that antibiotics administrated with L-Arg showed 10 to 100 fold greater activity in biolm reduction than antibiotics administrated alone, which may be associated with the ability of L-arginine to increase the metabolic rate of the bacteria remaining in the lower levels of biolm, especially in anoxic conditions. 44 Another study 45,46 also demonstrated the L-Arg antimicrobial properties realized through affecting their metabolic pathways. chitosan-arginine (Ch-Arg) complexes reduce E. coli O157 growth in lag or exponential phase.…”
Section: Antibacterial and Antifungal Activitiesmentioning
confidence: 98%
“…chitosan-arginine (Ch-Arg) complexes reduce E. coli O157 growth in lag or exponential phase. 45 Chitosan is a carbohydrate extracted from shellsh commonly used as an antimicrobial agent and food preservative. Chemical derivatives of chitosan with positively charged L-arginine may increase the surface charge density, thus, the Ch-Arg complex reveals greater antimicrobial effect against Gram-negative bacteria than unmodied chitosan.…”
Section: Antibacterial and Antifungal Activitiesmentioning
confidence: 99%